2017
DOI: 10.1007/s10461-016-1668-3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Social Affiliations and Healthcare Engagement Among Young, Black, Men Who Have Sex With Men

Abstract: Little work has examined how individuals' social affiliations-the venues in which they meet friends and engage in informal social interaction-influence their engagement with public health services. We investigate how links to these local places shape access to information and exposure to health-seeking behavior. Using longitudinal data from a respondent-driven sample of 618 young black men who have sex with men (YBMSM) in Chicago, we identify different sets of social venues that connect YBMSM. We then examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Our findings suggest BMSM are willing to initiate PrEP and that this decision can be supported with interventions and improved access to consistent healthcare .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Our findings suggest BMSM are willing to initiate PrEP and that this decision can be supported with interventions and improved access to consistent healthcare .…”
Section: Discussionmentioning
confidence: 70%
“…Our findings on initiation and adherence to PrEP are comparable to, or exceeded, those reported in large-scale PrEP randomized controlled trials [32,34] results provide additional data [33,41] that support the safety of daily oral PrEP among BMSM. Our findings suggest BMSM are willing to initiate PrEP and that this decision can be supported with interventions and improved access to consistent healthcare [5][6][7][8][9][10][11][12][13][14][15][16]42]. This is particularly salient in that this population faces multiple forms of structural inequalities and studies have shown that these barriers often influence PrEP uptake and utilization among Black MSM [41, [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV testing is the entrance point to a range of HIV prevention and treatment options, such as pre-exposure prophylaxis (PrEP) and ART (antiretroviral therapy) treatment, and is therefore a critical public health tool to help contain the HIV epidemic in the US [ 12 – 20 ]. It is crucial that individuals learn of HIV infection as immediately as possible, as those who are unaware of their HIV infection are more likely to transmit HIV to others due to higher viral loads and higher prevalence of sexual HIV transmission risk behaviors [ 2 , 8 , 21 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial that individuals learn of HIV infection as immediately as possible, as those who are unaware of their HIV infection are more likely to transmit HIV to others due to higher viral loads and higher prevalence of sexual HIV transmission risk behaviors [ 2 , 8 , 21 22 ]. Testing offers individuals who engage in high risk sex and receive a negative test result the opportunity to consider or adopt PrEP, a highly effective, biomedical HIV prevention method, learn about PEP and/or work towards other risk reduction strategies [ 12 13 , 23 25 ]. For these reasons, the Centers for Disease Control and Prevention (CDC) has recommended that MSM and transgender women who engage in certain risk behaviors test consistently or every 3–6 months [ 8 , 20 , 25 – 26 ].…”
Section: Introductionmentioning
confidence: 99%